Predictors of under-weight among children younger than 24 months in Nimule Border Town, Eastern Equatoria State, South Sudan: a community-based cross sectional study - Francis Eriga; Godfrey Gulom; John Bosco Alege (BMC, 2024)
Abstract Background Underweight is a public health problem globally, and more severe in South Sudan with wide sub-regional differences. In Nimule border town, which represents other border towns in South Sudan, data on underweight among children below two years is unavailable. Thus, this study set out to assess predictors of underweight among children younger than 24 months in Nimule border town, Magwi County, Eastern Equatoria State, South Sudan. Methods An analytical cross-sectional study was conducted in Nimule boarder town targeting 390 children younger than two years. Systematic sampling and simple random sampling methods were used. Data were collected through a researcher-administered questionnaire with both open and closed ended questions. Data was entered in EpiData and then exported into Statistical Package for Social Sciences research (SPSS) version 20 for analysis. Descriptive data analysis was conducted and data were summarized into frequencies and percentages, means with standard deviations, and medians with interquartile ranges. Bivariate analysis was conducted with the Chi-squared and Fisher's exact tests for categorical independent variables, and the student's t-test for numerical variables. Finally, multivariate analysis was done via logistic regression analysis and results were stated as odds ratios (OR) with corresponding 95% confidence interval (CI). The level of statistical significance was set at 5%. Results Out of the total 390 participants, 112 (28.7%) were under weight. The study showed primary (aOR, 0.38; 95% CI, 0.12-1.18; P = 0.095) and secondary (aOR, 0.37; 95% CI, 0.12-1.17; P = 0.091 levels of education were associated with underweight but not tertiary level of education (aOR, 0.76; 95% CI, 0.21-2.74; p = 0.671). Household income of 5000 to 10,000 (aOR, 0.26; 95% CI, 0.10-0.68; P = 0.006) and above 10,000 (aOR, 0.11; 95% CI, 0.04-0.28; P < 0.001) South Sudanese pounds, supplementary feeding before 6 months (aOR; 0.01; 95% CI, 0.02-0.05; P < 0.001) were associated with underweight and irregular hand washing (aOR; 2.17; 95% CI, 1.14-4.11; P = 0.018) was associated with increased odds of underweight. Conclusions This study established a high prevalence of underweight. Maternal level of education particularly primary, secondary, higher household incomes in excess of 5,000 South Sudanese pounds reduced the risk of underweight. While irregular hand washing was a risk factor for underweight.